The open-pit metallic extraction dilemma in Panama concerning “Minera Panamá”: between life’s sustainability and nature’s exploitation - Farinioni, Juan Pablo García; Reyes, Abdiel Rodríguez (Geografares, 2026)
The present article analyzes the sociopolitical crisis in Panama caused by the approval of Law 406 and its implications for the contract with Minera Panamá, S.A. Throughout 2023, the controversy over the lack of transparency and citizen participation in decision-making triggered massive social mobilizations, highlighting the involvement of social movements, trade unions, and young activists who demanded the defense of the environment and national sovereignty. The government’s response was to repeal the law and issue a landmark Supreme Court ruling declaring the mining contract unconstitutional for violating fundamental rights and constitutional provisions that protect natural resources and social welfare. We highlight the diverse positions that arise from the convulsive reality of open-pit metallic mining extractivism in Panama.